2007
DOI: 10.1126/science.1138632
|View full text |Cite
|
Sign up to set email alerts
|

Common Sequence Polymorphisms Shaping Genetic Diversity in Arabidopsis thaliana

Abstract: The genomes of individuals from the same species vary in sequence as a result of different evolutionary processes. To examine the patterns of, and the forces shaping, sequence variation in Arabidopsis thaliana, we performed high-density array resequencing of 20 diverse strains (accessions). More than 1 million nonredundant single-nucleotide polymorphisms (SNPs) were identified at moderate false discovery rates (FDRs), and approximately 4% of the genome was identified as being highly dissimilar or deleted relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

73
644
4
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 667 publications
(723 citation statements)
references
References 32 publications
73
644
4
2
Order By: Relevance
“…The ratio of non-synonymous to synonymous SNP was 1.45 and 1.39 in Daewon and Hwangkeum, respectively (Table 4). This ratio is similar to ratio shown in soybean (1.40) which is higher than those in Arabidopsis, maize, and sorghum and rice (Clark et al, 2007;Hufford et al, 2012;Lam et al, 2010;McNally et al, 2009;Nelson et al, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…The ratio of non-synonymous to synonymous SNP was 1.45 and 1.39 in Daewon and Hwangkeum, respectively (Table 4). This ratio is similar to ratio shown in soybean (1.40) which is higher than those in Arabidopsis, maize, and sorghum and rice (Clark et al, 2007;Hufford et al, 2012;Lam et al, 2010;McNally et al, 2009;Nelson et al, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…Based on the recently published whole genome resequencing of 20 Arabidopsis accessions using microarray data, 6 Zeller et al, also found that miRNAs that are not conserved outside of Arabidopsis have higher polymorphism than those that are. 5 This latter result, along with an observed increase in flanking variation at nonconserved miRNAs, suggests that these miRNAs may actually segregate as functional or nonfunctional in Arabidopsis, although this finding could also be due to the misidentification of nonconserved miRNAs.…”
mentioning
confidence: 99%
“…In this case, the GREEN or full immunity phenotype may be indicative of RPP13 which is known to recognize Emco5 and is closely linked to RPP1; however, this too has yet to be determined). Nonetheless, these preliminary data indicate that two of the most important RPP genes from previous laboratory research most likely occur in this natural population of A. thaliana as well as the matching avirulence effectors within the resident HpA population another 20 A. thaliana accessions (Borevitz et al 2007;Clark et al 2007), and a dramatic fall in the cost of DNA sequencing. The aspiration has progressed from plausibility to a very real and exciting opportunity.…”
Section: Resultsmentioning
confidence: 65%
“…In recent years, whole genome sequences have become publicly available from pioneering use of species like A. thaliana and Phytophthora sojae. And, this in turn has galvanized a Linnaeanlike approach by an international community of molecular biologists to name and classify all of the proteins encoded within an organism, one representa-tive organism at a time (Clark et al 2007;Holub 2006Holub , 2007Kamoun 2007;Tör 2008;Tyler et al 2006;Win et al 2007). This in effect is providing a powerful online catalogue of genes that enables further comparisons to be made among species (socalled comparative genomics).…”
Section: Divergent Enquiry From Early Revolutions In Plant Sciencementioning
confidence: 99%